AUDIT INVESTIGASI PEMBUKTIAN KERUGIAN KEUANGAN NEGARA OLEH BADAN PEMERIKSA KEUANGAN DALAM PENYIDIKAN KASUS KORUPSI: Investigation Audit of State Financial Loss Evidence by The Audit Board of Indonesia in Corruption Case Investigation - Andini, Siska Dwi (Fakultas Hukum, Universitas Trisakti, 2025)
Corruption is the main cause of state losses in managing state finances. According to ICW, there were 791 corruption cases in 2023, a 26.8% increase over 2022. There is no denying that the law enforcement activities conducted in investigative audits by APH and BPK together are inextricably linked to the disclosure of corruption cases. Since the duration of investigative audits varies widely, APH frequently decides to work with BPKP and the Inspectorate to coordinate investigative audits in order to determine state losses. The research was conducted using empirical legal methods, and the aim was to explain the investigative audit procedures carried out by BPK and the obstacles that exist in performing investigative audits. The research results show that BPK investigative audit refers to BPK Regulation Number 1 of 2020 and BPK RI Decree Number 2/K/I-XIII.2/4/2020. However, to overcome obstacles in obtaining sufficient and reliable evidence to prove state/regional losses, alternative procedures were developed for implementation, also using the Big Data Analysis system and the Digital Forensic Laboratory. BPK is expected to be able to standardize audit procedures, particularly alternative procedures, into technical guidelines and implementation instructions in order to further develop the accomplishments of investigative audits. Additionally, BPK is expected to fully support investigative audit-related resources in order to ensure quality and dependability of audit results.